Sociodemographic Factors Related to Food Security During COVID-19 Pandemic in Indonesia - Chica Riska Ashari; Vebby Amellia Edwin; Dyah Suryani; Sunarti Sunarti; Erni Buston; Hairil Akbar; Agnesia Clarissa Sera; Suyitno suyitno (International Journal of Public Health Science (IJPHS), 2022)
The condition of the COVID-19 pandemic with uncontrolled transmission led to the government implementing the Large-Scale Social Restrictions (PSBB) regulation. It was implemented to overcome the spread of COVID-19 and will also have an impact on community food security. The cross-sectional study aimed to examine socio-demographic factors and food security among communities during the COVID-19 pandemic in Indonesia. A total of 1,017 respondents partake in this rapid online survey. The result of multi logistic regression showed that who had stress or depression (Adj. OR = 2.81, 95% C.I = 2.03-3.89), poor dietary habit (Adj. OR = 1.94, 95% C.I = 1.46-2.57), and who live alone (Adj. OR = 6.53, 95% C.I = 2.99-14.25) strongly significant associated with poor food security. Who female of sex (Adj. OR = 1.47, 95% C.I = 0.04-2.07), no have working status (Adj. OR = 1.45, 95% C.I = 1.03-2.05), and not living on java island (Adj. OR = 1.35, 95% C.I = 1.02-1.83) have low associated correlation with poor food security. These findings suggested that the government should give intervention for communities that got stressed, have poor dietary habits, and those who live alone without family during pandemic COVID-19.